Penggunaan Media Audio Visual untuk Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan Siswa Kelas IV SD Negeri 016 Bangkinang Kota - Ananda, Rizki (Universitas Pahlawan Tuanku Tambusai, 2017)
Based on observations, indicating civic learning still conventionally implemented where teachers are still using instructional media were confined to the textbook. This causes make the students is not actice in the learning process and learning results obtained are low. Focused on the problem, this research aims to improve the planning, implementation and assessment of learning civics by using audio-visual media. This classroom action research using qualitative and quantitative approaches. In practice, this research consisted of two cycles was taken collaboratively with classroom teachers. Each cycle consists of planning, implementing measures are accompanied observations and reflections on each cycle. The research was conducted in the second semester of the academic year 2015/2016 in 016 Bangkinang City Elementary School with the research subjects were all students in fourth grade. The research data was collected through observation, interviews, field notes, documentation and test. The results of data analysis showed that the use of audio-visual media can improve student learning outcomes in learning in fourth grade Civics 016 Bangkinang City State. It is seen from (1) The results of student learning in the cognitive an increase of the average value of 7.1 in the first cycle to 8.0 in the second cycle, (2) the affective domain increased from an average value of 7.8 on I cycle to 8.5 in the second cycle, and (3) on psychomotor increased from an average value of 6.4 in the first cycle to 7.9 in the second cycle. Seeing the results of this study, the class action research in the use of audio-visual media in Civics learning needs to be applied and developed in order to improve the quality of education in the future.